Budaya Organisasi Sebagai Pemoderasi Pengaruh Partisipasi Penganggaran Pada Kinerja Anggaran Pemerintah Daerah Kabupaten Badung - Triani, A.A. Ayu Octa; Sujana, I Ketut (E-Jurnal Akuntansi, 2018)
This study aims to obtain empirical evidence of organizational culture as a moderator of the influence of budgetary participation on the performance of local government budget of Badung regency. The population used in this research is 15 departments in the Local Government Work Unit of Badung Regency. The sample in this research is determined by purposive sampling method. Data were collected using survey method. Data analysis technique used is Moderated Regression Analysis (MRA). The results showed that budgetary participation had an effect on the local government budget performance of Badung Regency. The results of moderation testing indicate that organizational culture is able to moderate the influence of budgetary participation on local government budget performance of Badung Regency, which means organizational culture strengthens the influence of budgetary participation in local government budget performance of Badung regency. Keywords: Budgetary Participation, Budget Performance, Organizational Culturesize, corporate social responsibility